2019
DOI: 10.1021/acs.orglett.9b03458
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Pd-Catalyzed Reductive Amination of Enolizable sp3-C–H Bonds

Abstract: A palladium-catalyzed reductive cyclization of nitroarenes has been designed to construct sp3-C–NHAr bonds from sp3-C–H bonds by using an enolizable nucleophile to intercept a nitrosoarene intermediate. Exposure of ortho-substituted nitroarenes to 5 mol % of Pd­(OAc)2 and 10 mol % of phenanthroline under 2 atm of CO constructs partially saturated 5-, 6-, or 7-membered N-heterocycles using α-pyridyl carboxylates, malonates, 1,3-dimethylbarbituric acid, 1,3-diones, or difurans as the nucleophile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The ubiquitous nature of N , N -diarylamines in molecules that exhibit important biological and material activities has spurred considerable research in developing efficient catalytic reactions to construct this important scaffold. , While transition metal-catalyzed cross-coupling reactions that form C–N bonds are legion, few examples exist of their use to make secondary N , N -diarylamines from nitroarenes. Our laboratory has developed a series of transition metal-catalyzed reactions that exploit the reactivity embedded in nitroarenes for the construction of C–NAr bonds via nitrosoarene reactive intermediates, and we were curious if a nitroarene could serve as the nitrogen component of the cross-coupling reaction . In 2002, Sapountzis and Knochel reported that diarylamines 3 could be constructed from nitroarenes via the nucleophilic addition of Grignard reagents to nitrosoarenes followed by an iron-mediated reduction of the N-oxide product. , After this seminal report, the development of reductive intermolecular cross-coupling reactions of nitroarenes lay dormant until 2015 when Baran and co-workers reported that 30 mol % of Fe­(acac) 3 catalyzed a reductive hydroamination reaction between a nitroarene and an olefin using superstoichiometric amounts of PhSiH 3 and Zn(0) as the reductant (Scheme ).…”
mentioning
confidence: 99%
“…The ubiquitous nature of N , N -diarylamines in molecules that exhibit important biological and material activities has spurred considerable research in developing efficient catalytic reactions to construct this important scaffold. , While transition metal-catalyzed cross-coupling reactions that form C–N bonds are legion, few examples exist of their use to make secondary N , N -diarylamines from nitroarenes. Our laboratory has developed a series of transition metal-catalyzed reactions that exploit the reactivity embedded in nitroarenes for the construction of C–NAr bonds via nitrosoarene reactive intermediates, and we were curious if a nitroarene could serve as the nitrogen component of the cross-coupling reaction . In 2002, Sapountzis and Knochel reported that diarylamines 3 could be constructed from nitroarenes via the nucleophilic addition of Grignard reagents to nitrosoarenes followed by an iron-mediated reduction of the N-oxide product. , After this seminal report, the development of reductive intermolecular cross-coupling reactions of nitroarenes lay dormant until 2015 when Baran and co-workers reported that 30 mol % of Fe­(acac) 3 catalyzed a reductive hydroamination reaction between a nitroarene and an olefin using superstoichiometric amounts of PhSiH 3 and Zn(0) as the reductant (Scheme ).…”
mentioning
confidence: 99%
“…Exposure of 92 to 5 mol % of Pd(OAc)2 and 10 mol % of phenanthroline in the presence of 2 atm of CO produced indoline 94, through the apparent attack of the electrophilic nitrosoarene with in situ generated enol 93. 44 In contrast to the reactivity of N-aryl metal nitrenes, five-, six-, and even seven-membered ring formation was possible using this reactivity pattern. We were able to leverage the ability of palladium(II) acetate to participate in directed C-H bond activation to achieve the functionalization of aryl C-H bonds to produce amides, such as 97.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While sp 2 C−N bond formation is possible with either nitrosoarenes through 6π electrocyclization reaction or N ‐aryl nitrenes through nitrene insertion reaction, the more challenging construction of sp 3 C−N bonds is extremely limited. For example, sp 3 C−H amination could be achieved using nitroarenes if the resulting nitrosoarene intermediate could be captured with a proximal nucleophile (Scheme 1b) [52] . Alternatively, allylic sp 3 C−H bonds could be aminated using transition metal catalysts under harsh reaction conditions (>150 °C and >40 atm CO) with poor functional group tolerance and low yields [53,54] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, sp 3 CÀ H amination could be achieved using nitroarenes if the resulting nitrosoarene intermediate could be captured with a proximal nucleophile (Scheme 1b). [52] Alternatively, allylic sp 3 CÀ H bonds could be aminated using transition metal catalysts under harsh reaction conditions (> 150 °C and > 40 atm CO) with poor functional group tolerance and low yields. [53,54] This scarce literature precedent clearly highlights the lack of methodologies exploiting the use of aryl nitro compounds as aminating reagents for the insertion into sp 3 CÀ H bonds.…”
Section: Introductionmentioning
confidence: 99%